Quality of Life and African American Women Who are Family Caregivers: A Literature Review with Implications for Psychiatric Mental Health Advanced Practice Registered Nurses. (3rd June 2018) - Starks, Shaquita A.; Outlaw, Freida; Graff, J. Carolyn; Likes, Wendy; White-Means, Shelley; Melaro, Laura; Wicks, Mona N.
ABSTRACT: Purpose: To identify factors affecting the quality of life (QOL) of African American women (AAW) family caregivers of individuals with kidney failure. Methods: Ferrans' Conceptual Model of QOL provided the framework for this literature review. Included studies were (a) peer- reviewed, (b) published within the last ten years, (c) written in English, and (d) examined QOL of AAW family caregivers. Using CINAHL© and PubMed©, we found 14 studies that described factors associated with these caregivers' QOL. Scope: Few studies document the QOL of AAW who are family caregivers, especially in the context of kidney failure. Psychiatric Mental Health Advanced Practice Registered Nurses need to learn about the factors influencing the QOL of these caregivers. Results: No studies were found within the last ten years that explored the QOL of AAW family caregivers of individuals with kidney failure. Findings reflected the QOL of AAW family caregivers in the context of other chronic conditions. Various factors such as stress, insomnia, and employment were linked to an impaired QOL. Implications for practice, research and education for PMH-APRNs are suggested. Conclusion: PMH-APRNs are uniquely trained to address many factors that affect the QOL of these caregivers and may provide holistic care aimed at promoting satisfactory QOL for these caregivers.